1984
DOI: 10.1016/s0006-3495(84)83995-8
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric behavior of DNA solution at radio and microwave frequencies (at 20 degrees C)

Abstract: The dielectric constant and conductivity of calf thymus DNA were investigated at frequencies between 0.1 MHz and 70 GHz. This work is to investigate the dielectric properties of DNA in low gigahertz region and also to study whether the dielectric behavior of the water is affected by the presence of highly charged DNA. The results of these measurements indicate the presence of two anomalous dispersions, the one between 1 MHz and 1 GHz and the second one above 1 GHZ. The dispersion at low frequencies is likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0
6

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 7 publications
7
48
0
6
Order By: Relevance
“…This observed dielectric behaviour was confirmed independently by Anagnostopoulou-Konsta et al [1988], who resolved two dispersions in DNA solutions using the method of thermally stimulated depolarization currents (TSDC), and more recently by Bone et al [1996] from dielectric data in the frequency range 10 -100 MHz. Two particularly interesting features of the small disper- sion are the very high activation energy (86 Ϯ 12 kJ/mole) and the fact that Figure 7 when extrapolated to T ϭ 293 K predicts a relaxation frequency of between 80 -90 MHz, as observed in the previous work [Takashima et al, 1984] carried out at 20 ºC. In other words, this dispersion preserves its characteristics through the change of state; freezing the substance does not apparently have any effect.…”
Section: Observations Relating To the Higher Frequency Dispersionsupporting
confidence: 60%
See 2 more Smart Citations
“…This observed dielectric behaviour was confirmed independently by Anagnostopoulou-Konsta et al [1988], who resolved two dispersions in DNA solutions using the method of thermally stimulated depolarization currents (TSDC), and more recently by Bone et al [1996] from dielectric data in the frequency range 10 -100 MHz. Two particularly interesting features of the small disper- sion are the very high activation energy (86 Ϯ 12 kJ/mole) and the fact that Figure 7 when extrapolated to T ϭ 293 K predicts a relaxation frequency of between 80 -90 MHz, as observed in the previous work [Takashima et al, 1984] carried out at 20 ºC. In other words, this dispersion preserves its characteristics through the change of state; freezing the substance does not apparently have any effect.…”
Section: Observations Relating To the Higher Frequency Dispersionsupporting
confidence: 60%
“…The pH was adjusted to 7.0 using Tris buffer. This method of sample preparation was used in order to correspond with that of Takashima et al [1984] at 20 ºC, so that direct comparison could be made. The complex permittivity measurements were made using a Hewlett Packard model 4192A impedance analyser, using a previously described technique [Bateman et al, 1992].…”
Section: Preparation Of Materials and Experimental Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown that DNA-in-water solutions have a strong relaxation point in the low MHz regime (32,33). This is typically considered to be due to counter ion movement around the transverse axis of the DNA molecule (34)(35)(36). Using 10 MHz and the movement of ions around the DNA molecule allows heating of a DNA-inwater solution at a much lower frequency than a traditional microwave heater.…”
Section: Methodsmentioning
confidence: 99%
“…The measurements can be divided between those studies that measured DNA above 1 MHz and those studies that measured at low frequencies (< 1000 Hz). Higher-frequency measurements were made by a number of authors [40,[89][90][91][92]. Low-frequency measurements have been made by Takashima, Sakamoto, Hanss, and Tung [16,20,32,93].…”
Section: Simple Model Of Dipole Momentmentioning
confidence: 99%